The Effect of a (Educational- Training) System Using the Stations Method in Developing the Level of Performance of Some Basic Skills of the Maysan Football Team Players - AL-Shareefi, Maytham Qasim Kadhim (International Journal of Psychosocial Rehabilitation, 2020)
In the introduction to the importance of the research, the researcher dealt with the importance of using the (educational- training) system to teach some basic football skills using the stations method, where knowledge is provided to the players during the training period. Help him to visualize the skill that Ti Jan Ha wants to see through her steps and her ability to understand those steps with a good level of intelligence and enjoy good health that helps him with motor and skill performance, and social peace through obtaining family support is the prominent role in the psychological support of the player. The research problem was that the use of known traditional methods that are constantly repeated sends boredom to learners or trainees alike, especially with younger age groups, and through the results of the posts on that school, they were tested against it by a special team for Maysan education without any development in the level of performance and accordingly, the diversity of training methods And the use of systems that support these methods and the diversity of measures taken during training is what the researcher worked on using an educational system based on the station method. The aim of the research is to prepare a (educational- training) program using the stations method and the effect of the system (educational- training) by using the stations in developing the performance level of some basic skills of the Maysan football educational team. The research imposed by the system for using (educational- training) for stations (B) has a significant effect on developing the performance level of some of the research sample's skills. There are also statistically significant differences between the pre and post tests of the research group in developing the level of performance of some basic skills of the research sample. The researcher used the experimental method. The research sample represented the players of the Maysan educational football team. The number of the sample was 16 players out of a total of 22 players, representing 75% of the research community. Pre-tests and dimensionless tests were performed after performing statistical procedures that were reached after the results of using the (training education) system using a positive effect method in learning basic football skills, and it was found that there are statistically significant differences in the STAT vision between the pre-tests and dimensional tests for the research group and in favor of the subsequent tests The researcher recommended using the educational training system for other age groups and other sports.